Berenstain Bears (The) / : Trouble with grownups - Berenstain, Stan (New York : Random House, 1992)
The squabbling in the Bear household between paretns and cubs subsides after Mama and Papa Bear and Brother and Sister perform humurous role-playing skits.
Keywords: Parent and child--Fiction; Role playing--Fiction; Bears--Fiction